Pulmonary nontuberculous mycobacterial infections and environmental factors: A review of the literature - Gardini, Giulia; Ori, Margherita; Codecasa, Luigi Ruffo; Matteelli, Alberto (Respiratory medicine, 2021)
Pulmonary nontuberculous mycobacterial (pNTM) infection is mainly acquired through the inhalation of bioaerosols. Nevertheless, behavioural restrictions are rarely given by clinicians to susceptible populations, in part because the available guidelines for pNTM management emphasize more diagnosis and treatment than prevention. Aim of this review is to clarify if pNTM prevention should routinely include recommendations about risk reducing behaviors. We used PubMed as biomedical database. We limited our search to the publication period 2000 to 2020 with selected keyword combinations including "nontuberculous mycobacteria", "water", "soil", and "exposure". Titles and abstract of selected articles were systematically screened. Articles were included in the analysis if they were published under free access through the digital library of the University of Brescia (Italy), and provided full text either in English, French, German or Italian. Articles were excluded if the topic was beyond the aim of our study. Finally, we selected 20 articles. Studies disagree in identifying the type of aerosol posing the highest risk for the development of pNTM infection. In the retrieved publications the colonization of household niches has been associated with a higher risk of pNTM disease, such as in the exposure to shower aerosols. Considering the non-household settings, the exposure to aerosols in indoor swimming and the higher soil exposure (>2 h/week) seem to correlate with a higher risk to develop pNTM disease. According to our findings, randomized behavioural intervention studies are missing. Stringent scientific evidence is missing to formulate recommendations on behavioural risk reduction for pNTM.